MITIGATE THE IMPACT OF SOCIAL MEDIA MISUSE ON JUNIOR SCHOOL TEENAGERS THROUGH SMART, WISE EDUCATION IN SOCIAL MEDIA - Alika; Mhd Safarudin Alhakim; Putri Rahmadhani Nasution; Salsabila Zahra Nst; Marlya Fatira; Ermyna Seri; Sri Wahyuni (Asian Journal of Islamic Economic Studies, 2025)
This community service program is carried out to mitigate the negative impacts of excessive social media activity on high school students. The aim is to improve the digital literacy of MTs Amaliyah Sunggal students. This program focuses on preventing the negative impacts of social media, such as cyberbullying and addiction, as well as teaching how to maintain privacy, avoid hoaxes, and maintain mental health. By involving students of the Medan State Polytechnic as facilitators, this activity offers educational seminars and training on digital literacy, provides time for using social media, and the importance of direct social interaction. A supervising lecturer supports the activity and produces scientific publications and educational videos. Through interviews with schools and knowledge transfer in academic seminars, this program provides educational solutions for the wise and safe use of social media. This activity costs IDR 618,000.00 (Six Hundred and Eighteen Thousand Rupiah). The activity results show decreased social media cases among students through interactive learning about internet ethics, risks, and impacts. In addition, students have a better understanding of the positive and negative impacts of social media. This program is expected to be sustainable through collaboration with various campuses in building digital literacy and intelligent and safe social media culture.